What is the median volume of intracerebral hemorrhage and is it changing?. Issue 5 (June 2022) - Robinson, David; Van Sanford, Carson; Kwon, Soo Young; Coleman, Elisheva; Sekar, Padmini; Murphy, Ryan; Flaherty, Matthew L; Demel, Stacie L; Aziz, Yasmin; Moomaw, Charles J; Haverbusch, Mary; Khoury, Jane; et al.
Objectives: Population-level estimates of the median intracerebral hemorrhage (ICH) volume would allow for the evaluation of clinical trial external validity and determination of temporal trends. We previously reported the median ICH volume in 1988. However, differences in risk factor management, neuroimaging, and demographics may have affected ICH volumes. The goal of this study is to determine the median volume of ICH within a population-based cross-sectional study, including whether it has changed over time. Methods: The Genetic and Environmental Risk Factors for Hemorrhagic Stroke study was a population-based study of ICH among residents of the Greater Cincinnati/Northern Kentucky region from 2008 through 2012. This study utilizes those data and compares with ICH cases from the same region in 1988. Initial computed tomography images of the head were reviewed, and ICH volumes were calculated using consistent methodology. Results: From 2008 through 2012, we identified 1117 cases of ICH. The median volume of ICH was 14.0 mL and was lower in black (11.6) than in white (15.5) patients. Median volumes of lobar and deep ICH were 28.8 mL and 9.8 mL, respectively. Median ICH volume changed significantly from 1988 to 2008–2012, with age-and-race-adjusted volume decreasing from 18.3 mL to 13.76 mL (p = 0.025). Conclusions: Median volume of ICH was 13.76 mL, and this should be considered in clinical trial design. Median ICH volume has apparently decreased from 1988 to 2008–2012.